Choice of Insulin Coformulations: Biphasic Insulin Versus Insulin-GlP1RA - Sanjay Kalra; Sambit Das; Saptarshi Bhattacharya; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
This communication presents a pragmatic approachto describe the phenotypes which match with preferential usage of dual phase insulin or basal insulin+ glucagon-like peptide 1 receptor agonist (GLP1RA)coformulations. A comprehensive evaluation,including severity and style of glycaemia, clinical presentation, comorbidities, complications, and culinary preference, allows efficient choice of insulin formulation. This framework helps in initiation,intensification and interchange of injectable therapy,in an apt, and ept, manner. Keywords: BIAsp, GLP1RA, glargine, insulin, Biphasic insulin, IGlarLixi, lixisenatide, IDegAsp, LisproMix,IDegLira, person centred care, premixed insulin.